Shyness and its relationship to the five major personality factors (A field study on a sample of students from the University of Al-Furat) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
this research aims to detect the correlation between shyness ,and the five major personality factors among a sample of fourth –year students from the University of Al Furat where the number of members of the research sample were (150) students from the colleges  of education in Al Hassakah, Der Eizor and ALRaqa , and tries identify the degree of shyness and identify the differences due to sex in all of shyness and the five major personality factors. The researcher used in his research two scales: the first is shyness scale  by Hussein Dorrainy B.T(1999). The second is the five major personality factors by costa and Mc Crae(1992) ,and after testing the hypotheses was reached following results:1- Students of  the college  of education have high shyness.2-  There is a positive correlation statistically significant at the 0.05 level between shyness and Neuroticism.3- There is a negative  correlation statistically significant at the 0.05 level between shyness and(Extraversion, Openness, Agreeableness, and Conscientiousness).4- There are no differences due to sex in all of shyness and the five major personality factors(Neuroticism, Extraversion, Openness, Agreeableness, and Conscientiousness).